Pengaruh Inokulasi Gabungan Beberapa Vegetative Compatibility Group Isolat Fusarium oxysporum f.sp.cubense Pada Pisang Ambon hijau - Sherli Trinitia; Nasril Nasir; - Jumjunidang; Catur Hermanto; - Riska (Universitas Andalas, 2013)
The aim of this study was to determine level of virulency of several Vegetative Compatibility Group (VCG) of Fusarium oxysporum f. sp. cubense (Foc) isolates against cv Ambon hijau. The study was conducted at the laboratory of plant diseases and screen house of Solok Tropical Fruit Research Institute from August 2012 to February 2013.The experiment was arranged in randomized block design with seven treatments and four replications, each treatment consisted of fiveplants. The treatments were the mixture of isolates FocVCG 01213/16, 0121, and 0124/5 andthe single. The results revealed that several VCG isolates of Foc grouped in race 1 and 4 inoculated in single or mixture caused the highest disease incidence with the percentage of wilt was 100%. The fastest incubation period of disease on cv Ambon hijau caused by isolate VCG 01213/16 (5.95days), followed by VCG (11.35 to 12 days), single isolate of VCG 0121 (13.15 days) and VCG 0124/5 (17.45 days). Keywords :banana, Fusarium oxysporum f. sp. cubense, Vegetative Compatibility Group, inoculation